INTERNSHIP FOR PROFESIONAL CAREER: LEARNING FROM VOCATIONAL HIGH SCHOOL 1 KADEMANGAN BLITAR EAST JAVA - Kalim Mustofa; Muhammad Aris Ichwanto; Moh. Khoerul Anwar; Dai Weifen; Asryan Ani; Setyanto Putro; Yoto; Widiyanti (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2021)
Internship is a stage of education in Vocational High Schools that trains students to adapt to the business world and practice the competencies they learn in school directly in the industrial world. But unfortunately, not all vocational students who take part in internship programs in the industrial world can be well received. This study wants to look more deeply into how strategic management empowers Vocational High Schools in preparing students for the internship. This research uses mixed methods, more specifically the Embedded Design. Samples were taken randomly as many as 61 teachers and 353 students using the random sampling technique. Through SPACE Matrix analysis, it is known that the appropriate strategy in developing schools is to support an aggressive approach, namely by implementing the SO (Strategy to use power to reach opportunity) strategy. So it can be explained that the profile of Vocational High School 1 Kademangan is stable and can continue to prepare internship students with plans to take advantage of existing opportunities to improve the quality of education.